Helicobacter pylori: the Progression of Gastritis to Stomach Cancer - Abdulla, Namaat R.; Khudair , Zainab W.; T.S, Al-Amery; Abdulla, Noor R. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Gastric cancer remains one of the most prevalent malignancies worldwide, with nearly one million new cases and over 700,000 deaths annually, largely linked to Helicobacter pylori infection. This gram-negative bacterium colonizes the gastric mucosa, causing chronic gastritis that can progress to malignancy. Specific Background: H. pylori is recognized as a Class I carcinogen by the International Agency for Research on Cancer due to its strong association with gastric adenocarcinoma. The infection triggers inflammatory and genetic responses that facilitate carcinogenesis through bacterial, host, and environmental interactions. Knowledge Gap: Despite decades of research, the molecular mechanisms linking H. pylori virulence factors to gastric epithelial transformation and the synergistic role of host and environmental cofactors remain insufficiently elucidated. Aims: This study reviews how H. pylori infection progresses from gastritis to gastric cancer by detailing bacterial virulence determinants, host inflammatory responses, and environmental contributors. Results: Key virulence factors such as CagA, VacA, BabA, and OipA disrupt epithelial integrity, modulate signaling pathways (e.g., NF-κB, Wnt/β-catenin), and trigger cytokine overexpression, fostering neoplastic changes. Novelty: The review integrates molecular, immunologic, and environmental dimensions of H. pylori pathogenesis, highlighting their collective role in carcinogenic transformation. Implications: Understanding these multifactorial mechanisms underscores the need for early detection, eradication therapies, and targeted prevention strategies to reduce gastric cancer mortality.Highlight : H. pylori infection can progress from gastritis to gastric cancer through chronic inflammation and mucosal damage. The bacterium’s virulence factors and host immune response play crucial roles in disease progression. Early detection and eradication of H. pylori are vital to prevent gastric cancer development. Keywords : Helicobacter Pylori, Gastritis, Gastric Cancer, Virulence Factors, Cytokines